Is Listed Corporates Financial Performance Vulnerable? ROE Factors measurement Using DuPont Formula - Ricordel, Pascal; Majlath, Melinda (European Journal of Sustainable Development, 2019)
It’s been 10 years since the last financial crisis, and the rising in stock market price along with record dividends raises deep concerns about the sustainability of listed corporate financial performance. Has the narrow logic of shareholder value been compromising long term financial performance leading to a financial crisis? We question here the DuPont equation to track financial performance drivers over time for discussing about its vulnerability. A disaggregated five-steps DuPont equation is used to set up following drivers: operational profitability, asset turnover, leverage multiplier, interest and fiscal burden. We draw a statistical analysis of those drivers with a panel data of 43 international non-financial corporates from France, Germany, Hungary and Italy between 2012 and 2017. The results stress the role of fiscal burden, interest burden and operational profit as the main ROE driver. Leverage multiplier driver, consensually considered as more financially vulnerable, has played an astonishing negative role. The drop in asset turnover is however the more worried signal as this factor is the most sustainable. Keywords: ROE components, DuPont equation, Financial sustainability, Listed corporate performance, Financial reporting